Meningkatkan kemampuan menulis puisi dengan menerapkan Teknik Imagine (khayalan visual) di kelas X IPA SMAN Bernas Pangkalan Kerinci - Rosidah, Rosidah (Universitas Serambi Mekkah, 2020)
The purpose of this research is to improve the ability to write poetry by applying the imagine (visual imagination) technique at the Bernas Pangkalan Kerinci High School. Based on the results of data analysis, it can be concluded that the imagine (visual fantasy) technique can improve poetry writing skills at the Bernas Pangkalan Kerinci State High School, Pelelawan Regency. The results showed that there was an increase in the average value of writing poetry of students from the first cycle, 58 with a good category to 85 with a very good category in the second cycle. This is indicated because the teacher has understood how to carry out the learning process using the imagine technique (visual delusion), and students are familiar with the method. Suggestions from researchers that all teachers must use a variety of learning methods so that students get used to and the learning process takes place fun.